The impact of information and communication technology (ICT) on economic growth in the OIC countries - Majid Aghaei; Mahdieh Rezagholizadeh (Economic and Environmental Studies (E&ES), 2017)
New growth theories hypothesize economic growth processes as heavily dependent on investment in Information and Communication Technology (ICT). However, the full empirical verification of this hypothesis still is an open task, particularly when growth is considered within selected countries such as the OIC countries. Furthermore, the conclusions derived from research concerning the causal relationship between ICT and economic growth is often sensitive to the research methodology employed. This paper employs dynamics and static panel data approach within a framework of growth model and apply them to the economy of OIC countries over the time period of 1990-2014. The estimates reveal a significant impact of investments in ICT on economic growth in the countries considered. The policy implication of this paper is that the OIC countries should design specific policies for promoting investment in ICT.
Keywords: O33; C23; 330; ICT; OIC Countries; Panel Data; Economic Growth